Implementasi Perilaku Organisasi di Madrasah Aliyah Negeri Keterampilan - Asmira, Asmira; Kurnia , Dela; Asmendri, Asmendri; Sari , Milya (Indo-MathEdu Intellectuals Journal, 2024)
Organizational behavior in Madrasah Aliyah Negeri (MAN) Skills are very helpful and support the achievement and realization of the vision of the madrasah well and effectively. Organizational Behavior (PO) is a field of study that studies the interaction of individuals, groups and organizations in the context of work. PO can help MAN Skills improve their effectiveness by understanding and managing the behavior of teachers and employees and students. The main purpose of this article is to explain the concept and purpose of PO, provide examples of how PO can be implemented in MAN skills, discuss the benefits of implementing PO in MAN Skills. This research uses a qualitative approach through the literature study method. Research data is sourced from various literature, namely scientific articles, books, and other relevant scientific sources. The data analysis technique used in this study is content analysis. The results of the data analysis concluded that PO is an important style for MAN Skills to improve its effectiveness and competitiveness. By implementing PO effectively and sustainably, MAN skills can achieve its vision to become a madrasah of excellence and character